Infrastructures, Economic Development and Health - Abbasi, Mansoureh (Université d'Ottawa / University of Ottawa, 2023)
Chapter 1- We offer the first causal evidence on the effect of high-speed Internet on sexual behaviour, and HIV spread in Africa. Exploiting the gradual connection of the Internet network to the submarine Internet cables in Africa's coastal regions in combination with individual-level data, we apply difference-in-differences and find that exposure to fast Internet reduces the likelihood of HIV infection in locations close to the Internet network. The effect is significantly larger for women, educated individuals, older adults, and urban residents. The analysis of causal mechanisms reveals that, while access to fast Internet increases the likelihood of early sexual initiation and extramarital relationships, it also increases knowledge of HIV prevention and transmission, the use of modern methods of contraception, reduces fertility, and the likelihood of being in a polygamous marriage. We do not find that employment status, occupational choice, or migration drives the effect of the fast Internet on HIV. In addition, we use google trends data to show that Internet access increases the search popularity of sex-related topics, contraception, and HIV/AIDS. The findings imply that the expansion of Internet networks in Africa requires educational policies to promote healthy and stable intimate connections. Chapter 2- We combine longitudinal data on the financial activities of individuals with information on temporal and spatial variations in broadband diffusion in the United States in recent years to study the causal impact of high-speed Internet on financial decisions. Our identification strategy controls for individual fixed effects and uses lightning strike density as an instrument for broadband penetration. We find that broadband diffusion increases the probability of investment in the stock market, having a mortgage, and having an active savings account. Analyzing causal mechanisms, we find that access to broadband Internet increases financial literacy and the use of financial services such as online banking and having a financial advisor. Additionally, heterogeneity analysis shows that the effect of broadband penetration on stock market participation significantly differs by gender, age, marital status, education, income, level of social connection, and mental health status. Analyzing the interconnection between financial decisions provides novel insights into the well-known stock market participation puzzle in the United States. We show that the probability of investing in the stock market is lower for an individual with a mortgage payment. Also, the probability of participation in the stock market is higher for a person with active savings. Chapter 3- Evidence for road expansion and electrification as drivers of job creation is limited and mixed, with most studies considering either one or the other and only in isolation. We estimate the average and heterogeneous impacts of road and electricity investments and the interaction of the two on job creation over the past two decades in 27 countries of sub-Saharan Africa. Exploiting the exogenous location of ancestral ethnic homelands, we introduce a new instrumental variable for road accessibility inspired by post-independence leaders' agenda of building roads to extend authority over their country's entire expanse and promote nation-building. we used the topography and lightning strikes, a key source of damage to electric lines and disruption of service, to instrument the electricity supply. We find that constructing new roads and electricity grids positively and significantly affects employment from higher access to roads and electric grids. Moreover, the interaction between access to the two enhances the effects, making them complementary investments. The impacts of both individual and bundled investments are positive, but with differences between men and women, workers of various ages, and countries at different stages of development. In urban areas, better access to roads and electricity promotes employment, mostly related to the skilled base job creation. In rural areas, greater access induces a transition from low-to high-skilled occupations. These differential effects suggest that the structural transformation brought about by road and electricity expansion is primarily a rural phenomenon.
Keywords: Infrastructures; Economic development; HIV; Household's finance; Road and electricity; Employment